With Active Multidisciplinary Teams and Regular Exchange of Information Within Services, to More Effective Integration of Roma in the Local Community - Košir, Gregor (10. Nacionalna konferenca o varnosti v lokalnih skupnostih: Mirna, varna in inkluzivna družba ter varnost v lokalnih skupnostih, 2024)
In the chapter, we focus on presenting the importance of multidisciplinary teams and the regular exchange of information within services with the aim of more effective integration of Roma into local communities. The good practices municipal administration with assistance of the Centre for Social Work, the Labour Office, the Police, the Intermunicipal Inspectorate and Municipal Wardens, kindergartens and schools, as well as the Probation Administration of the Republic of Slovenia, which contribute to the more successful integration of Roma in the municipality of Kočevje, are presented. In the conclusion of the paper, the challenges for the integration of the Roma community in the future and the issue of financing programs intended for education, employment and integration of Roma into the local community are presented.